Copyright of Architectural Works - Mario Dominik Burić; Marko Spahija (Elektronički Zbornik Radova Veleučilišta u Šibeniku)
In this paper, the authors present a complete insight into the legal regulation of copyright over architectural works. Along with the presentation of the current legislative framework, a historical overview of the legal regulation of copyright over architectural works in the territory of today's Republic of Croatia and its development is presented. The legal regulation of copyright over architectural works is discussed according to the new, currently valid Law on Copyright and Related Rights, with a simultaneous insight and comparison with the relevant provisions of the Law on Construction, which is in force at the time of writing this paper. Special attention has been given to the legal regulation of contracting for the creation of architectural works and the relationship between the Law on Copyright and Related Rights and the Law on Construction in the case of amendments to building permits. In addition to the presentation of the relevant legislation, recent domestic case law in legal issues of the relationship between public procurement and copyright and the right to use an architectural work is also presented, which case law can be useful primarily to legal practitioners, and then to investors and architects, as well as all those who participate in construction projects in some capacity. The legal arrangements of copyright over architectural works in the comparative legal systems of two countries, the Republic of Slovenia and the Republic of Serbia, are presented in an overview.